Functional outcome and quality of life index after endonasal versus external dacryocystorhinostomy - Rashmi A Dave; Suryasnata Rath; Devjyoti Tripathy; Samir Mahapatra; Mohd Hasnat Ali (Indian Journal of Ophthalmology, 2025)
Purpose: To compare the functional outcome and quality of life (QOL) index following non-endoscopic endonasal dacryocystorhinostomy (NEN-DCR) and external dacryocystorhinostomy (EXT-DCR). Methods: Patients were prospectively allocated to two groups. All adult patients presenting with primary nasolacrimal duct obstruction (PANDO) undergoing EXT-DCR and NEN-DCR at a tertiary eye care center were included. Patients in one group underwent EXT-DCR and others NEN-DCR. Functional outcomes were measured by Munk Score and fluorescein dye disappearance test (FDDT). A validated quality of life questionnaire (EQ-5D-3L) in the local language (Odiya) was used to measure health status (social impact score) before and 1 day, 2 weeks, 6 weeks, and 3 months after surgery. The primary outcome measure was the functional outcome–Munk Score and secondary outcome measures included the QOL index and the FDDT. Results: A total of 110 patients were recruited and equally distributed (n = 55) in both groups. The mean age of the population was 47.6 years (SD = 14.02; range 20–79 years). The majority (71%, 79/110) were female. When longitudinally followed over time, functional outcome and QOL index showed reasonably rapid and marked improvement in both groups after surgery compared to baseline scores. The Munk score (P = 0.037) and QOL index (P = 0.007) were marginally better on the first postoperative day for the NEN-DCR group compared to EXT-DCR but comparable at all subsequent visits. At a median follow-up of 9 weeks (range: 0.5–24 weeks), the anatomical outcome was comparable between both groups. Conclusion: Our results demonstrate that functional outcome and QOL index show rapid and marked improvement in both NEN-DCR and EXT-DCR after surgery. NEN-DCR outcomes were marginally better on the first postoperative day but comparable to EXT-DCR thereafter.